2019
DOI: 10.1128/msphere.00408-19
|View full text |Cite
|
Sign up to set email alerts
|

Single-Strand Annealing Plays a Major Role in Double-Strand DNA Break Repair following CRISPR-Cas9 Cleavage in Leishmania

Abstract: CRISPR-Cas9 genome editing relies on an efficient double-strand DNA break (DSB) and repair. Contrary to mammalian cells, the protozoan parasite Leishmania lacks the most efficient nonhomologous end-joining pathway and uses microhomology-mediated end joining (MMEJ) and, occasionally, homology-directed repair to repair DSBs. Here, we reveal that Leishmania predominantly uses single-strand annealing (SSA) (>90%) instead of MMEJ (<10%) for DSB repair (DSBR) following CRISPR targeting of the miltefosine trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 80 publications
(156 reference statements)
2
59
0
Order By: Relevance
“…The most active sgRNAs (sets 5 and 6) were the same in L. braziliensis and L. donovani , indicating that the sgRNA sequence had an impact on the gene targeting efficiency. This is in line with a recent study that tested the efficiency of three gRNAs targeting identical sequences of the miltefosine transporter gene in L. donovani , L. major , and L. mexicana , and found the relative gRNA activity to be the same [ 31 ]. Studies in other systems revealed that sgRNA sequence features such as position-specific nucleotide composition, GC content, motifs located in the sgRNA “seed” region, and secondary structures of sgRNAs contribute to sgRNA efficacy [ 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The most active sgRNAs (sets 5 and 6) were the same in L. braziliensis and L. donovani , indicating that the sgRNA sequence had an impact on the gene targeting efficiency. This is in line with a recent study that tested the efficiency of three gRNAs targeting identical sequences of the miltefosine transporter gene in L. donovani , L. major , and L. mexicana , and found the relative gRNA activity to be the same [ 31 ]. Studies in other systems revealed that sgRNA sequence features such as position-specific nucleotide composition, GC content, motifs located in the sgRNA “seed” region, and secondary structures of sgRNAs contribute to sgRNA efficacy [ 80 , 81 , 82 , 83 , 84 ].…”
Section: Discussionsupporting
confidence: 88%
“…Second, the generation of CRISPR-derived null mutants is facilitated by the use of donor DNA repair cassettes (containing antibiotic selection markers) flanked by short homology arms targeting the gene of interest (GOI), in a single transfection [ 17 , 29 ]. Third, both single and multigene families can be targeted with this system [ 16 , 30 ], and it even allows simultaneous editing of multiple loci [ 24 , 30 ], as well as the identification of essential genes [ 20 , 30 , 31 ]. CRISPR gene editing also allows for in situ addition of flanking loxP sites to a gene of interest and the subsequent rapamycin-inducible gene deletion by dimerisable Cre (DiCre) recombinase [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations